If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(2x + 3) = 3(2x + 2) Reorder the terms: 2(3 + 2x) = 3(2x + 2) (3 * 2 + 2x * 2) = 3(2x + 2) (6 + 4x) = 3(2x + 2) Reorder the terms: 6 + 4x = 3(2 + 2x) 6 + 4x = (2 * 3 + 2x * 3) 6 + 4x = (6 + 6x) Add '-6' to each side of the equation. 6 + -6 + 4x = 6 + -6 + 6x Combine like terms: 6 + -6 = 0 0 + 4x = 6 + -6 + 6x 4x = 6 + -6 + 6x Combine like terms: 6 + -6 = 0 4x = 0 + 6x 4x = 6x Solving 4x = 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 4x + -6x = 6x + -6x Combine like terms: 4x + -6x = -2x -2x = 6x + -6x Combine like terms: 6x + -6x = 0 -2x = 0 Divide each side by '-2'. x = 0 Simplifying x = 0
| 2x=(x-4)(x-4) | | -8+18m=46 | | -3x+8y=-16 | | 18sin(x)(cos(x)-1)=0 | | 1+8c=6c+21 | | 3p=9p | | -x+8x+32=0 | | 4p+10=90 | | 86-m=4 | | 12-2(a-1)=5 | | -4(2x-6)+5=-8x+29 | | 4w-15=17 | | 1998*9878= | | 5x+4x-3x-5=31 | | 5(j-2)=2j+6 | | 15-5XL=25 | | 2x*2+3x-90=0 | | rx=x | | 3x-26=24 | | 2+5(X+3)-3(X-4)=2(2X+4) | | 2x+13x=60 | | 8-4y=0 | | 54=24+5b | | x^2+4x+y^2-4y-8=0 | | 4y-9(y-5)/6 | | 10/10x=-12/20 | | 11-(4-6)+5(13y+1)=9 | | -3(3z+8)-4(2z+5)-5z= | | 2(x-4)-8=-8 | | -5(3z-4)+4z=-4 | | 21x-109=206 | | (x+50)=y |